Ibrahim Miiteferrika's-Embassy of Poland and His Unknown Ambassadorial Account - (:unkn) unknown (ISAM, 2016)
As a sophisticated intellectual, one of the least known aspects of Ibrahim Muteferrika, the founder of Turkish printing press, is his service as a diplomat. Ibrahim Muteferrika went to Poland and undertook negotiations during a time when the Ottoman Empire was fighting against Austria and Russia. However, hitherto we have not had much information about this particular diplomatic mission. In this article, we will examine his embassy to Poland between December 1736 and February 1737 under the light of contemporaneous historical sources and archival documents, through his ambassadorial account dedicated to this mission which we have recently discovered.
Keywords: Ibrahim Milteferrika; Poland; Chief Hatman; Diplomacy; Ambassadorial Account